2015
DOI: 10.4102/phcfm.v7i1.892
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of community care workers about key family practices in a rural community in South Africa

Abstract: BackgroundInterventions by community care workers within the context of community-based integrated management of childhood illness (CIMCI) may have a positive effect on child health if the health workers have adequate knowledge about key family practices.SettingThe study was conducted in rural areas of the West Coast district in the Western Cape, South Africa.ObjectivesThe objective of this study was to determine the knowledge of community care workers about five of the 16 key family practices of CIMCI.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
1
2
1
Order By: Relevance
“…It is worth noting that the IMCI-only intervention group did not exhibit a significant decrease in the number and/or percentage of U-5 NMF patients prescribed antibiotics. This finding contradicts previous studies which found that IMCI courses increased providers’ adherence to guidelines related to antibiotic distribution based on patient need [ 30 ]. It should be considered, however, that this finding may be influenced by the small sample size of the IMCI-only group in comparison to the other study groups.…”
Section: Discussioncontrasting
confidence: 99%
“…It is worth noting that the IMCI-only intervention group did not exhibit a significant decrease in the number and/or percentage of U-5 NMF patients prescribed antibiotics. This finding contradicts previous studies which found that IMCI courses increased providers’ adherence to guidelines related to antibiotic distribution based on patient need [ 30 ]. It should be considered, however, that this finding may be influenced by the small sample size of the IMCI-only group in comparison to the other study groups.…”
Section: Discussioncontrasting
confidence: 99%
“…Many studies have shown that healthcare providers in low and middle-income countries have limited training to manage maternal complications, including eclampsia (Sana Sheikh et al, 2016) and some of them did not have IST for over five-years (Wanduru et al, 2016). The finding from this research mirrors the results in several other studies across multiple geographic contexts, presenting a poor provision of ongoing training is commonplace and mentioned (Stellenberg et al, 2015). As concluded by a multi-national analysis from several countries in sub-Saharan Africa that the current provision of refresher training courses was ‘not sufficient to meaningfully improve the quality of care in these countries’, it is considered to assess the effectiveness of training programmes from the perspective of the individual CHW and the health system in which they operate (Sana Sheikh et al, 2016).…”
Section: Discussionsupporting
confidence: 87%
“…All our FGDs comprised CHWs belonging to at least two different facilities or two different WBPHCOTs. CHWs identifying as home-based caregivers (HBCGs), peer educators, community caregivers (CCGs) in KwaZulu-Natal and community-care workers (CCW) in the Western Cape ( Friedman, 2005 ; Stellenberg et al , 2015 ) were considered eligible to participate in the FGDs if they were 18 years of age and older, agreed to participate and provided written informed consent.…”
Section: Methodsmentioning
confidence: 99%